2023
DOI: 10.1007/s10639-023-11683-y
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation, and evaluation of an online supported peer feedback module to enhance students’ argumentative essay quality

Abstract: We know little to what extent peer feedback strategies can be applied on a large scale in higher education for complex tasks. This study aimed to design, implement, and evaluate an online-supported peer feedback module for large-scale use to enhance higher education students’ argumentative essay writing performance. To do this, 330 students from five different courses at bachelor and master levels followed the online supported peer feedback module. In this module, students were asked to write an argumentative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…According to Carless (2006), feedback is integral to learning and involves communication about a gap between actual performance and desired outcomes. A synthesis of over 500 meta‐analyses identified feedback as one of the most critical factors in improving student achievement (Hattie & Timperley, 2007; Noroozi, Biemans, & Mulder, 2016; Noroozi et al, 2023). In addition, many studies have shown that feedback has positive effects on learners' motivation (Burgers et al, 2015), achievement (Carter, 2009; Foley et al, 2019) and performance in the learning process (Gielen & De Wever, 2015; Latifi et al, 2021; Van der Kleij et al, 2015).…”
Section: Discussion and Avenues For Future Researchmentioning
confidence: 99%
“…According to Carless (2006), feedback is integral to learning and involves communication about a gap between actual performance and desired outcomes. A synthesis of over 500 meta‐analyses identified feedback as one of the most critical factors in improving student achievement (Hattie & Timperley, 2007; Noroozi, Biemans, & Mulder, 2016; Noroozi et al, 2023). In addition, many studies have shown that feedback has positive effects on learners' motivation (Burgers et al, 2015), achievement (Carter, 2009; Foley et al, 2019) and performance in the learning process (Gielen & De Wever, 2015; Latifi et al, 2021; Van der Kleij et al, 2015).…”
Section: Discussion and Avenues For Future Researchmentioning
confidence: 99%
“…Jongsma et al (2023) conducted a comparative analysis of online and offline peer feedback in ten empirical studies, and discovered that online peer feedback is more effective, especially in the aspect of writing skill developments. The positive effects of student participation in online peer feedback (OPF) activities on writing development have also been observed among EFL university students in Indonesia (Wahyudin, 2018) and the Netherlands (Noroozi, Banihashem, Biemans, Smits, Vervoort & Verbaan, 2023). To ensure positive outcomes in OPF, Yang (2016) suggests providing students with a foundational comprehension of main ideas via scaffolding, facilitating knowledge exchange through both giving and receiving feedback, and resolving writing issues through revisions guided by peer feedback.…”
Section: Students' Engagements In Online Peer Feedback (Opf) Activitiesmentioning
confidence: 99%
“…Good technology design can also help in improve the quality of skills such as argumentative writing, according to Noroozi et al (2023). This is because, if PA feedback is presented in an appropriate way, it can facilitate reflection to improve original work in situations with the backward assessment process (Misiejuk and Wasson, 2021).…”
Section: Introductionmentioning
confidence: 99%